2012
DOI: 10.1149/2.044212jes
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fe (II) Species in Electrolyte on Performance of Graphite Anode for Lithium-Ion Batteries

Abstract: Iron dissolution into an electrolyte from the olivine LiFePO 4 in the lithium-ion cell has been recently investigated. In order to study the influence of the dissolved Fe 2+ species in electrolyte on the lithium intercalation/deintercalation into an artificial graphite electrode, the electrochemical behavior of graphite was investigated in 1 mol L −1 LiPF 6 electrolyte solution containing Fe 2+ species. The cells containing Fe 2+ species showed larger reversible capacity loss than the Fe-free cells. Electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…It is reported that the orientation of graphite particles affects the reversible capacity of anode, namely, lessoriented graphite particles display a lower reversible capacity (Shim and Striebel, 2004). This is due to the low orientation of particles, which brings difficulties in kinetics of lithium insertion and leads to the formation of new boundaries between particles through the irreversible interaction of lithium ions and electrolyte (Rhodes et al, 2011;Lai et al, 2012). Furthermore, the content of hexagons changes during cycling while the layered structure of graphite maintains unchanged, and this change substantially leads to the performance degradation (Andersson et al, 1999;Ridgway et al, 2012).…”
Section: Degradation Mechanismmentioning
confidence: 99%
“…It is reported that the orientation of graphite particles affects the reversible capacity of anode, namely, lessoriented graphite particles display a lower reversible capacity (Shim and Striebel, 2004). This is due to the low orientation of particles, which brings difficulties in kinetics of lithium insertion and leads to the formation of new boundaries between particles through the irreversible interaction of lithium ions and electrolyte (Rhodes et al, 2011;Lai et al, 2012). Furthermore, the content of hexagons changes during cycling while the layered structure of graphite maintains unchanged, and this change substantially leads to the performance degradation (Andersson et al, 1999;Ridgway et al, 2012).…”
Section: Degradation Mechanismmentioning
confidence: 99%
“…The origin of this observation is not entirely clear yet, but might indicate inhomogeneous deposition of V. The transition metals V and Fe act as catalysts at the anode surface for the formation and subsequent growth of the SEI [6,43]. The deposition of transition metals is in addition hindering the Li intercalation into the graphite anode by clogging anode pores [14,43,44]. The increase of the surface layer related resistance was analyzed using EIS in [26].…”
Section: Chemical Compositions Of Anode Close-to-surface Materials Andmentioning
confidence: 99%
“…It has been recently observed that Mn nanoparticles are present within cracks in the graphite, suggesting that Mn compounds can be deposited internally [21]. In addition, surface structural disordering in the graphite due to deposition of iron has been observed [43]. Although the observed Mn content may be associated with an artifact of the sputtering process that can cause the re-deposition of sputtered Mn, there is a strong possibility that Mn ions are deposited at the interlayer spaces between graphene layers or cracks in graphite, which may inhibit the contraction and expansion of the graphite during the intercalation/deintercalation process.…”
Section: Spatial Distribution Of Deposited Mn Compounds At the Graphimentioning
confidence: 99%